Anomalously high geothermal flux near the South Pole. Issue 1 (December 2018) - Jordan, T.; Martin, C.; Ferraccioli, F.; Matsuoka, K.; Corr, H.; Forsberg, R.; Olesen, A.; Siegert, M.
Abstract Melting at the base of the Antarctic Ice Sheet influences ice dynamics and our ability to recover ancient climatic records from deep ice cores. Basal melt rates are affected by geothermal flux, one of the least constrained properties of the Antarctic continent. Estimates of Antarctic geothermal flux are typically regional in nature, derived from geological, magnetic or seismic data, or from sparse point measurements at ice core sites. We analyse ice-penetrating radar data upstream of South Pole revealing a 100 km long and 50 km wide area where internal ice sheet layers converge with the bed. Ice sheet modelling shows that this englacial layer configuration requires basal melting of up to 6 ± 1 mm a−1 and a geothermal flux of 120 ± 20 mW m−2, more than double the values expected for this cratonic sector of East Antarctica. We suggest high heat producing Precambrian basement rocks and hydrothermal circulation along a major fault system cause this anomaly. We conclude that local geothermal flux anomalies could be more widespread in East Antarctica. Assessing their influence on subglacial hydrology and ice sheet dynamics requires new detailed geophysical observations, especially in candidate areas for deep ice core drilling and at the onset of major ice streams.